Integrasi Nilai-Nilai Pendidikan Islam Dalam Pembelajaran Anak Usia Dini DI TK AL Gholib Al Ikhlas Balung Jember: Integration of Islamic Educational Values ​​in Early Childhood Learning at AL Gholib Al Ikhlas Balung Jember - Mufida Gunawati (Qudwah: Journal of Islamic Education, 2026)
This study aims to identify Islamic educational values ​​and analyze their implementation in early childhood at the TK IT Al Gholib Al Ikhlas Balung Jember. This study is a field study using a qualitative approach involving early childhood as research subjects. Data were collected through direct observation, interviews, and documentation, then analyzed using a flowchart analysis model. The results indicate that the Islamic educational values ​​developed include aspects of faith, worship practices, and moral formation. These values ​​are implemented through learning materials covering the Quran, Hadith, creed, worship, morals, Prophetic teachings, and the introduction of Arabic and English vocabulary. To enhance the effectiveness of the learning process, educators implement a variety of Islamic education-based learning methods, utilize learning media as supporting tools, and involve parents through parenting programs as part of strengthening children's character education.